2007
DOI: 10.1111/j.1460-9568.2006.05253.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased N‐acetyl‐aspartate levels in anterior cingulate and hippocampus in subjects with post‐traumatic stress disorder: a proton magnetic resonance spectroscopy study

Abstract: The purpose of this study was to investigate the concentration of N-acetyl-aspartate (NAA) in the brain and its relationship with clinical characteristics in patients with post-traumatic stress disorder (PTSD). Proton magnetic resonance spectroscopy was performed in order to measure NAA concentrations in the anterior cingulate cortex (ACC) and bilateral hippocampus in 26 subjects with fire-related PTSD, who were survivors of a subway fire in South Korea, and 25 age- and sex-matched healthy comparison subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 34 publications
3
40
1
Order By: Relevance
“…Increased NAA/Cr ratios were found in right DLPFC of 15 GAD patients compared to healthy controls, although the use of ratio analyses hinders direct comparability between studies. In major depression, most studies have failed to detect cortical NAA abnormalities (51), although in PTSD, hippocampal NAA reductions have been reported even in the absence of volumetric reductions (52)(53)(54). Our correlational results at study endpoint add to an emerging literature relating NAA concentrations to anxiety variables, though the directionality and regional localization of the findings have been inconsistent across studies.…”
Section: Discussionmentioning
confidence: 37%
“…Increased NAA/Cr ratios were found in right DLPFC of 15 GAD patients compared to healthy controls, although the use of ratio analyses hinders direct comparability between studies. In major depression, most studies have failed to detect cortical NAA abnormalities (51), although in PTSD, hippocampal NAA reductions have been reported even in the absence of volumetric reductions (52)(53)(54). Our correlational results at study endpoint add to an emerging literature relating NAA concentrations to anxiety variables, though the directionality and regional localization of the findings have been inconsistent across studies.…”
Section: Discussionmentioning
confidence: 37%
“…Hippocampal volumes have been inversely associated with verbal memory deficits (Bremner et al, 1995), combat exposure severity (Gurvits et al, 1996), dissociative symptom severity (Bremner et al, 2003a;Stein et al, 1997), depression severity (Villarreal et al, 2002a), and PTSD symptom severity (Bremner et al, 2003a;Gilbertson et al, 2002;Villarreal et al, 2002a). Spectroscopy studies of hippocampus have reported decreased NAA in the hippocampus, often interpreted as consistent with decreased neuronal integrity (Brown et al, 2003;Freeman et al, 1998;Ham et al, 2007a;Mohanakrishnan Menon et al, 2003;Schuff et al, 2001;Villarreal et al, 2002b). The results of two studies suggest that hippocampal volumes may increase following treatment with serotonin reuptake inhibitors (Bossini et al, 2007;Vermetten et al, 2003).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 95%
“…Magnetic resonance spectroscopy (MRS) studies have revealed diminished N-acetyl aspartate (NAA) levels in the ACC in PTSD (De Bellis et al, 2001b, b;Ham et al, 2007a;Mahmutyazicioglu et al, 2005;Schuff et al, 2008). Furthermore, NAA levels in the pregenual ACC were negatively correlated with the severity of reexperiencing symptoms (Ham et al, 2007a).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 97%
See 1 more Smart Citation
“…The midfrontal cortex VOI was positioned anterior to the genu of the corpus callosum, and was centered on the midline on the axial plane and on the bicommissural line on the sagittal plane, as described earlier (Ham et al, 2007;Sung et al, 2007) (Figure 1). …”
Section: Mri/mrs Acquisition and Processingmentioning
confidence: 99%